2013
DOI: 10.1097/icl.0b013e31827d4f25
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Release Phenomena in Contact Lens Care by Silicone Hydrogel Lenses

Abstract: Contact lens solutions are highly complex mixtures of biocides (preservatives), surfactants, and other agents designed to disinfect, clean, and wet contact lenses. The commercialization of silicone hydrogel (SiHy) lenses has resulted in unique challenges to the manufacturers of contact lens solutions, because the properties of these materials differ markedly from those seen previously with poly-hydroxyethyl methacrylate-based hydrogels. Historically, hydrogel lens uptake and release of low-molecular weight pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 57 publications
(63 reference statements)
0
33
0
Order By: Relevance
“…Imayasu et al 31 demonstrated that cultured human corneal epithelial cells treated with MPS containing poloxamine and boric acid showed discontinuous and disrupted ZO-1 staining at cell-cell borders using laser confocal microscopy versus the normal continuous linear staining pattern seen in control non-MPS-exposed cells. 32 Similarly, Chuang et al 16 demonstrated changes in ZO-1 staining as well as disturbed patterns of occludin staining when corneal epithelial cell monolayers were exposed to various MPS, with the poloxamine and boric acid-buffered solution having the greatest impact. In addition to the in vitro findings, Paugh and colleagues 39 used fluorescein penetration in human subjects as a measure of barrier function decline.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Imayasu et al 31 demonstrated that cultured human corneal epithelial cells treated with MPS containing poloxamine and boric acid showed discontinuous and disrupted ZO-1 staining at cell-cell borders using laser confocal microscopy versus the normal continuous linear staining pattern seen in control non-MPS-exposed cells. 32 Similarly, Chuang et al 16 demonstrated changes in ZO-1 staining as well as disturbed patterns of occludin staining when corneal epithelial cell monolayers were exposed to various MPS, with the poloxamine and boric acid-buffered solution having the greatest impact. In addition to the in vitro findings, Paugh and colleagues 39 used fluorescein penetration in human subjects as a measure of barrier function decline.…”
Section: Discussionmentioning
confidence: 96%
“…16,31 These laboratory-based findings are confounded by the controversial clinical observation of fluorescein staining of the human cornea following wear of various lens-MPS combinations and the role of lens-solution biocompatibility. 29,32 Corneal fluorescein staining has been reported to be maximal after 2 to 4 hours of contact lens wear, suggesting that this may represent the time point at which the cornea is most vulnerable to solution-induced effects. 33 The purpose of this study was to investigate the impact of MPS on the rabbit corneal surface in vivo after 2 hours of lens wear and the corresponding effects of lens-released MPS on the ability of PA to invade the corneal epithelium.…”
mentioning
confidence: 99%
“…There is a strong possibility that this effect is different with silicone hydrogel lenses because they have more compact polymer matrix with lower water content, have smaller pore sizes, and are mostly nonionic. 46 Although there was not a significant difference in corneal staining between saline solution and the other multipurpose solutions (besides RevitaLens) in short-term use, there was an overall trend suggesting that saline solution contributed to less epithelial change of the cornea. It is possible that a longer exposure would lead to a larger difference in corneal staining between saline solution and the other multipurpose solutions.…”
Section: Discussionmentioning
confidence: 83%
“…Beyond the initial qualification of the contact lens material, the overall biocompatibility of a multipurpose contact lens disinfecting solution (MPS) with the contact lens material also needs to be defined. It is recognized that contact lens materials uptake and release some components of MPS, which may in turn affect ocular cell response [19][21]. Most notably, lens-solution interactions have been shown to be of critical importance in patterns of solution induced corneal staining as seen in both the StainingGrid and the IER Matrix Study [22], [23].…”
Section: Introductionmentioning
confidence: 99%